2020
DOI: 10.7150/jca.46721
|View full text |Cite
|
Sign up to set email alerts
|

Complement sC5b-9 and CH50 increase the risk of cancer-related mortality in patients with non-small cell lung cancer

Abstract: Objectives: Immunologic dysfunction occurred in most of patients with non-small cell lung cancer (NSCLC), which worsened the overall survival (OS) of patients. Complement activation plays a significant role in abnormal activation of immune system. However, the prognostic value of complement components such as CH50 and sC5b-9 in NSCLC patients remains unclear. This study evaluated the risk factors of NSCLC and created a prediction model. Methods: A real-world study was conducted including data from 928 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Previous studies have demonstrated that a number of complement components can be used as biomarkers for lung cancer diagnosis and determination of prognosis (33,34). Complement components have recently been regarded as biomarkers in predicting mortality risk in NSCLC (35). Oner et al (36) demonstrated that C3b and C4d levels are Nomograms are intuitive methods for visualizing risk prediction models (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that a number of complement components can be used as biomarkers for lung cancer diagnosis and determination of prognosis (33,34). Complement components have recently been regarded as biomarkers in predicting mortality risk in NSCLC (35). Oner et al (36) demonstrated that C3b and C4d levels are Nomograms are intuitive methods for visualizing risk prediction models (42,43).…”
Section: Discussionmentioning
confidence: 99%